Endogenous Growth and the Manufacturing Revolution - LEUNG, Hing-Man (Institutional Knowledge at Singapore Management University, 2002)
Manufacturing is undergoing a revolution. Teamwork, job-rotation, multitasking are superseding the Taylorist mode of organization. The skilled workforce, armed with automated machines, is gradually substituting and replacing the unskilled. At the same time the U.S. economy is experiencing record breaking growth. Is faster growth a consequence of this manufacturing revolution? We study this by inserting dynamic career choice into endogenous growth by human capital accumulation. The answer is affirmative: The gradual substitution of the unskilled by the skilled boosts the long-term growth trend. The model also explains worsening wage inequality between as well as within the skilled groups.